2021
DOI: 10.3390/cells10051038
|View full text |Cite
|
Sign up to set email alerts
|

The ECM Modulator ITIH5 Affects Cell Adhesion, Motility and Chemotherapeutic Response of Basal/Squamous-Like (BASQ) Bladder Cancer Cells

Abstract: This study aims at characterizing the role of the putative tumor suppressor ITIH5 in basal-type bladder cancers (BLCA). By sub-classifying TCGA BLCA data, we revealed predominant loss of ITIH5 expression in the basal/squamous-like (BASQ) subtype. ITIH5 expression inversely correlated with basal-type makers such as KRT6A and CD44. Interestingly, Kaplan–Meier analyses showed longer recurrence-free survival in combination with strong CD44 expression, which is thought to mediate ITIH-hyaluronan (HA) binding functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Recently, Huth et al proposed the formation of HA cable-like structures by ITIH5 in the skin [13]. Additionally, the prognostic significance of ITIH5 has been demonstrated in bladder cancer in close association with abundant CD44 expression; matching this observation, SCaBER bladder cancer cells abundantly expressing CD44 could be sensitized to cisplatin treatment after forced ITIH5 expression in vitro [18].…”
Section: Introductionmentioning
confidence: 82%
“…Recently, Huth et al proposed the formation of HA cable-like structures by ITIH5 in the skin [13]. Additionally, the prognostic significance of ITIH5 has been demonstrated in bladder cancer in close association with abundant CD44 expression; matching this observation, SCaBER bladder cancer cells abundantly expressing CD44 could be sensitized to cisplatin treatment after forced ITIH5 expression in vitro [18].…”
Section: Introductionmentioning
confidence: 82%
“…ITIH5 is known as a tumor suppressor gene for various cancers (breast cancer, bladder cancer, pancreatic cancer, etc.). 45 , 46 , 47 In recent years, some studies have found that ITIH5 is the major ITIH family member expressed in human skin and is a natural stabilizer of hyaluronic acid. 48 The complex formed by ITIH5 and HA stabilized HA and promoted the formation of ECM structure, meanwhile regulating inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…ITIH5 is known as a tumor suppressor gene for various cancers (breast cancer, bladder cancer, pancreatic cancer, etc.) 45–47 . In recent years, some studies have found that ITIH5 is the major ITIH family member expressed in human skin and is a natural stabilizer of hyaluronic acid 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Rose et al showed that the prognostic value of ITIH5 expression in basal cell type MIBC was closely related to the expression of CD44. 28 Overexpression of ITIH5 could inhibit the growth and migration of BLCA cells in the case of high expression of CD44. However, the role of ITIH5 in p53-like BLCA remains to be studied.…”
Section: Introductionmentioning
confidence: 99%